Dzień Pański w nauczaniu św. Cezarego z Arles w świetle studium jego "Kazań do ludu" - Pochwat, Józef (Vox Patrum, 2013)
Speaking about the Lord’s Day, saint Caesar of Arles († 543) explains to the faithful the importance of this day and other religious holidays. Going to church has a social dimension and clearly distinguishes Christians from Pagans. Bishop of Arles attaches much importance to the fact that Christians systematically and regularly attend church services, care about punctuality and do not leave the church before the end of the Mass. St Caesar, being an experienced pastor, instructs the faithful how to behave in the church. He shows the difference between Christianity and Paganism. Christians celebrate on Sunday, Pagans on Thursday in honour of Jupiter. He asks the faithful not to conduct any court cases on Sunday and abstain from work. Bishop of Arles put the Eucharist in the centre of the Lord’s Day. He teaches that the Eucharist is true Body and Blood of Christ. He points out that the Holy Communion is like medicine for a human being, for his body and his soul, hence the concern of the Bishop so that faithful receive the Eucharist with a pure heart. A necessary condition for receiving of the Eucharist is to forgive a neighbour.